(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Chief and senior nurses hold a vital position in the leadership and management of urban family clinics, which deliver essential healthcare services, particularly to underserved populations. Evaluating their performance status is essential for maintaining and improving the quality, effectiveness, and efficiency of healthcare delivery within these clinical settings.